Double lesion of TFCC injury from penetrating wrist trauma: A case report - Thanat Charoenpol; Tulyapruek Tawonsawatruk (Trauma Case Reports)
Bony avulsion injuries of the triangular fibrocartilage complex (TFCC) caused by penetrating wrist trauma are rare, and there is limited literature available regarding their treatment. This case report describes a 54-year-old male who sustained a penetrating injury to his right wrist, resulting in “double lesion” of TFCC injury, which are ulnar avulsion (Palmer 1B) and radial avulsion (Palmer 1D) lesion with a sigmoid notch fracture. The patient underwent an arthroscopic examination and a novel arthroscopic technique for fixation and repair of the TFCC injury. The procedure involved debridement, repair of the dorsal radioulnar ligament bony avulsion, and fixation of the foveal bony avulsion of the TFCC. The patient's wrist was immobilized postoperatively, followed by gradual rehabilitation. At the final follow-up of six months, the patient demonstrated improved range of motion and functional outcomes. This case report highlights the successful use of arthroscopic techniques for the treatment of complex TFCC avulsion injuries resulting from penetrating wrist trauma.